PERFORMANCE GAUGING OF PORTFOLIO: LUENBERGER DISTANCE FUNCTION APPROACH ON SARAJEVO STOCK EXCHANGE (The South East European Journal of Economics and Business, 2019)
Efficiency measurement of economic phenomena is of great importance to economists. Known terms and concepts from microeconomic theory and data envelopment analysis regarding efficiency have been developed and adapted to cater different questions and areas of economics. This paper focuses on applications in the area of finance, more specifically, portfolio optimization and Markowitz model. The paper has two goals. First is to give a concise overview of the theoretical and empirical research regarding Luenberger shortage (distance) function in portfolio optimization. The second goal is to empirically evaluate efficiency of a portfolio on the Sarajevo Stock Exchange (SSE). The contribution of the paper is the first comprehensive evaluation of sources of inefficiencies of a portfolio which is not positioned on the efficient frontier on the SSE, as well as Balkan region. The results of the analysis show that efficiency can be obtained with rebalancing the initial portfolio with the inclusion of transaction costs as well.